Direct limits on the Bs0 oscillation frequency - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Agelou, M.; Agram, J. L.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; et al. (American Physical Society (APS), 2006)
We report results of a study of the Bs0 oscillation frequency using a large sample of Bs0 semileptonic decays corresponding to approximately 1fb-1 of integrated luminosity collected by the D0 experiment at the Fermilab Tevatron Collider in 2002-2006. The amplitude method gives a lower limit on the Bs0 oscillation frequency at 14.8ps-1 at the 95% C.L. At Δms=19ps-1, the amplitude deviates from the hypothesis A=0 (1) by 2.5 (1.6) standard deviations, corresponding to a two-sided C.L. of 1% (10%). A likelihood scan over the oscillation frequency, Δms, gives a most probable value of 19ps-1 and a range of 17<Δms<21ps-1 at the 90% C.L., assuming Gaussian uncertainties. This is the first direct two-sided bound measured by a single experiment. If Δms lies above 22ps-1, then the probability that it would produce a likelihood minimum similar to the one observed in the interval 16-22ps-1 is (5.0±0.3)%. © 2006 The American Physical Society.